Treatment of metabolic syndrome in the early period after kidney transplantation in patients with chronic renal failure - O. N. Rzhevskaya; N. V. Zagorodnikova; K. E. Lazarev; A. V. Pinchuk (Трансплантология (Москва))
This paper describes the observation of 47 patients suffering from various kidney diseases and related metabolic syndrome. The evaluation of disorders of metabolic changes is carried out and a set of preventive measures including the use of non-drug means (not smoking, diet, physical rehabilitation), and drug therapy (statins, insulinotherapy if necessary) is proposed. Studies have shown that successful kidney transplantation in patients suffering from a chronic renal failure, coupled with the metabolic syndrome when using the complex measures aimed at the treatment of metabolic disorders can significantly improve the quality of life of patients.